(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between a generalized topological space and a bitopological space, namely upper (lower) weakly μ(σ_1,σ_2)-continuous multifunctions, has been defined and studied. Moreover, several characterizations and some properties concerning upper weakly μ(σ_1,σ_2)-continuous multifunctions and lower weakly μ(σ_1,σ_2)-continuous multifunctions are established. Furthermore, the relationships between almost μ(σ_1,σ_2)-continuity and weak μ(σ_1,σ_2)-continuity are considered.